2017
DOI: 10.6008/spc2179-6858.2017.003.0016
|View full text |Cite
|
Sign up to set email alerts
|

A qualidade da água de dessedentação animal e a preservação das áreas de preservação permanente

Abstract: No meio rural as interferências nos recursos hídricos estão relacionadas à destruição das áreas de preservação permanentes devido à utilização de agrotóxicos, manejo inadequado do gado e de seus dejetos. As áreas de preservação permanente (APPs) são fundamentais na busca pelo desenvolvimento sustentável, minimizam os impactos da ação pluvial, eólica no solo e garantem a preservação da biodiversidade, estabelecendo o equilíbrio do ambiente. O estudo objetivou analisar a qualidade físico-química e microbiológica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 6 publications
(6 reference statements)
0
7
0
Order By: Relevance
“…In a study on water quality in 15 milk producing rural properties in the TV, Bortoli et al (2017) found that cattle are raised loose, with free access to the place of watering, which is carried out in watercourses on the properties where this resource was present. Access to these sites was related to the presence of pasture areas and potters close to the watercourses, a characteristic observed, in the present study, in properties rated Very Bad, Bad and Regular, which present pasture areas both in the PPAs and in the recovery strips along the watercourses.…”
Section: Discussion Of Datamentioning
confidence: 99%
See 4 more Smart Citations
“…In a study on water quality in 15 milk producing rural properties in the TV, Bortoli et al (2017) found that cattle are raised loose, with free access to the place of watering, which is carried out in watercourses on the properties where this resource was present. Access to these sites was related to the presence of pasture areas and potters close to the watercourses, a characteristic observed, in the present study, in properties rated Very Bad, Bad and Regular, which present pasture areas both in the PPAs and in the recovery strips along the watercourses.…”
Section: Discussion Of Datamentioning
confidence: 99%
“…Access to these sites was related to the presence of pasture areas and potters close to the watercourses, a characteristic observed, in the present study, in properties rated Very Bad, Bad and Regular, which present pasture areas both in the PPAs and in the recovery strips along the watercourses. Bortoli et al (2017) observed that this access result in trampling on the margin, causing siltation, compaction and erosion, in addition to contamination of the water with coliforms by the defecation of cattle on the site, which affects water quality and contributes to the spread of diseases. The absence of native vegetation also contributes to the transport of waste to water resources, increasing contamination.…”
Section: Discussion Of Datamentioning
confidence: 99%
See 3 more Smart Citations